2018
DOI: 10.1007/s00417-018-3905-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in retinal ischemic post-conditioning

Abstract: Post-C is a complex molecular signaling process with a multitude of altered molecular pathways. We identified potential gene candidates in Post-C. Studying the impact of altering expression of these factors may yield insight into new methods for treating or preventing damage from retinal ischemic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
(84 reference statements)
2
7
0
Order By: Relevance
“…Retinae were harvested 10 days after ischemia, shortly after our electrophysiologic assessments of functional outcome at 7 days postischemia, so the proteome profiles reported here do not necessarily represent the acute phase of a dynamic postischemic response nor ones representative of long-term recovery, but somewhere intermediate between the two. To this point, few of the changes in the retinal protein profile we measured in response to ischemia, with and without parental RHC, were found at the RNA level in response to ischemia, with and without postconditioning, in rats 41 ; the same is true for respective pathway analyses in this and our study. However, beyond species differences, this is not necessarily unexpected given that we measured retinae at 10 days postischemia and Roth's group measured at 1 day postischemia, and that mRNA abundance does not necessarily translate to protein abundance.…”
Section: Discussionsupporting
confidence: 72%
“…Retinae were harvested 10 days after ischemia, shortly after our electrophysiologic assessments of functional outcome at 7 days postischemia, so the proteome profiles reported here do not necessarily represent the acute phase of a dynamic postischemic response nor ones representative of long-term recovery, but somewhere intermediate between the two. To this point, few of the changes in the retinal protein profile we measured in response to ischemia, with and without parental RHC, were found at the RNA level in response to ischemia, with and without postconditioning, in rats 41 ; the same is true for respective pathway analyses in this and our study. However, beyond species differences, this is not necessarily unexpected given that we measured retinae at 10 days postischemia and Roth's group measured at 1 day postischemia, and that mRNA abundance does not necessarily translate to protein abundance.…”
Section: Discussionsupporting
confidence: 72%
“…KEGG analysis also showed that the NF-kappa B signaling pathway, Jak-STAT signaling pathway, Toll-like receptor signaling pathway, PI3K-Akt signaling pathway, TNF signaling pathway, MAPK signaling pathway, Calcium signaling pathway, cAMP signaling pathway, and Apoptosis were significantly enriched. These findings were in agreement with previous studies [12,[35][36][37][38][39][40][41]. Different expression profile between RIRI and DHF+RIRI revealed reversed pathways responsible for DHF treatment.…”
Section: Discussionsupporting
confidence: 93%
“…(i) Intravitreal administration: An intravitreal injection of MSCs is feasible as a means to reach the dysfunctional retinal ganglion cells. Injection of MSCs into the vitreous in a rodent model rescued the retina from ischemic damage by suppression of apoptosis, preserved autophagy, and attenuation of inflammation and vascular permeability [ 59 61 ]. Intravitreally transplanted MSCs may also function by donating functional mitochondria to retinal ganglion cells [ 62 ].…”
Section: Main Textmentioning
confidence: 99%